Upaya Mewujudkan Kepatuhan Wajib Pajak yang Lebih Baik: Peran Pengetahuan Perpajakan dan Lokus Kendali Internal - Utami Puji Lestari; Didit Darmawan (Jurnal Simki Economic, 2023)
Taxpayer compliance plays a crucial role in the country's economic development and financing of various public programs. However, knowledge of taxation remains a factor that also influences the level of taxpayer compliance. Adequate tax knowledge can help taxpayers understand their tax obligations and carry them out correctly. In addition, internal locus of control can also affect taxpayer compliance. Internal locus of control refers to an individual's perception of the level of control they have in carrying out their tax responsibilities. Strong perception of internal locus of control can increase motivation and personal responsibility in fulfilling tax obligations. Deepening related to understanding the effect of tax knowledge and internal locus of control on taxpayer compliance is the goal of his research. There was involvement from 100 respondents who were students from an agency where they worked as permanent employees. The accidental sampling technique was determined to be the sampling technique in this study. The collected data was then analysed using regression analysis assisted by a software called SPSS. It is hoped that the results of this study for related parties can add to their insights and become a recommendation, especially for taxpayer compliance, especially from student groups to increase because they have also worked and have status as permanent employees in an agency.